Demonstration of polarization pulling in a fiber-optical parametric amplifier - Stiller, Birgit; Morin, Ph; Nguyen, D. M.; Fatome, J.; Maillotte, H.; Pitois, S.; Sylvestre, T. (Optics InfoBase Conference Papers, 2012)
We report the experimental demonstration of all-optical polarization pulling of an initially polarization-scrambled signal using a fiber-optical parametric amplifier. Nonlinear polarization pulling has been achieved for both the signal and idler with 25 dB gain. © 2012 OSA.
CRIS-Team Scopus Importer:2021-06-29